Analysis of Biobanked Serum from a Mycobacterium avium subsp paratuberculosis Bovine Infection Model Confirms the Remarkable Stability of Circulating miRNA Profiles and Defines a Bovine Serum miRNA Repertoire. - Ronan G Shaughnessy; Damien Farrell; Karel Riepema; Douwe Bakker; Stephen V Gordon (PLoS ONE)
Johne's Disease (JD) is a chronic enteritis of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). Current disease control strategies are hampered by the lack of sensitive and specific diagnostic modalities. Therefore, novel diagnostic and prognostic tools are needed, and circulating microRNAs (miRNAs) may hold potential in this area. The aims of this study were twofold: (i) to address the stability of miRNA in bovine sera from biobanked samples, and (ii) to assess the potential of miRNAs as biomarkers for JD disease progression. To address these aims we used bovine sera from an experimental MAP infection model that had been stored at -20°C for over a decade, allowing us to also assess the stability of miRNA profiles in biobanked serum samples through comparison with fresh sera. Approximately 100-200 intact miRNAs were identified in each sample with 83 of these being consistently detected across all 57 samples. The miRNA profile of the biobanked sera stored at -20°C for over 10 years was highly similar to the profile of <1 year-old sera stored at -80°C, with an overlap of 73 shared miRNAs. IsomiR analysis also indicated a distinct bovine serum-specific isomiR profile as compared to previously reported bovine macrophage miRNA profiles. To explore the prognostic potential of miRNA profiles cattle defined as seropositive for anti-MAP antibodies (n = 5) were compared against seronegative cattle (n = 7). No significant differential expressed miRNAs were detected at either the early (6 months) or late (43, 46 and 49 months) intervals (FDR≤0.05, fold-change≥1.5) across seropositive or seronegative animals. However, comparing pre-infection sera to the early and late time-points identified increased miR-29a and miR-92b abundance (2-fold) that may be due to blood-cell population changes over time (P<0.001). In conclusion our study has demonstrated that bovine circulating miRNAs retain their integrity under long-term sub-optimal storage temperatures opening the way for increased miRNA analyses from biobanked samples for a range of infectious and non-infectious diseases.